Effect of the development of distinctive power as quickly as in the level of defensive basketball skills - Suomom, Ali (Journal of Physical Education, 2012)
Characterized by the game of basketball as one of the games that require the practitioners performance skills with certain specifications and technique accurately,linked to the performance of those skills requirements of the private and the most important of these requirements is the force deals quickly, and it appears evident in the skills defense after the performance of the attack on the basket of competitor, and there search aims to work exercises to prepare for the development of private power dealsas quickly as the basketball players as well as to identify the impact of the development of distinctive force as soon as the level of performance in defense of the basketball players applicants, to help basketball coaches to maintain the level of performance skill defense.And that the most important to him Matousel Abajt:1. The impact of an effective strength training in the development of distinctive force as soon as the arms and legs.2. The force of the evolution of distinctive speed of the arms and the two menin strumental in the development of the performance level of defensive basketball players.